2009
DOI: 10.1111/j.1440-1681.2008.05118.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygenation Applied Immediately After Coronary Occlusion Reduces Myocardial Necrosis and Acute Mortality in Rats

Abstract: 1. Because in ischaemia there is a critical lack of O2, it has been reasoned that increasing O2 delivery to the ischaemic myocardium could serve as adjunctive therapy for acute myocardial infarction (MI). Accordingly, in the present study, the effect of early hyperbaric oxygenation (HBO) on mortality and MI size after coronary occlusion was examined in rats. 2. After coronary occlusion, male Wistar rats were randomly assigned to receive either HBO for 1 h in a hyperbaric chamber (100% O(2) at 253 kPa; n = 106)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…Similar results were reported earlier [7]: the authors observed a decrease in the necrosis zone in the myocardium if HBO procedure was performed immediately after ischemia and then the rats were kept under standard conditions for 24 h. We suppose that the problem of HBO application in acute MI is at the stage of accumulation of experimental and clinical material. Heterogeneity of the experimental and clinical models and different variants of HBO application do not allow defi nite conclusions.…”
Section: Resultssupporting
confidence: 85%
“…Similar results were reported earlier [7]: the authors observed a decrease in the necrosis zone in the myocardium if HBO procedure was performed immediately after ischemia and then the rats were kept under standard conditions for 24 h. We suppose that the problem of HBO application in acute MI is at the stage of accumulation of experimental and clinical material. Heterogeneity of the experimental and clinical models and different variants of HBO application do not allow defi nite conclusions.…”
Section: Resultssupporting
confidence: 85%
“…Six weeks after the surgical ligation of the coronary artery or sham operations, the animals were anesthetized as described above and measurements were performed using a 12-MHz transducer connected to a HP Sonos-5500 echocardiograph (Hewlett-Packard, California, USA) as previously described 14,15 . The MI size was measured by transversal 2-dimensional view of the left ventricle on the basal, midtransversal, and apical planes.…”
Section: Methodsmentioning
confidence: 99%
“…Although it identifies the presence of an MI-dependent electrically inactive area, the ECG is not a method that can quantify the infarction area 2 . The echocardiogram can determine the presence and the size of the MI with very good sensitivity [3][4][5][6][7][8][9][10][11][12][13][14][15] , even in periods as early as two days after necrosis, and it also provides information about deviant atrial and ventricular function. The best method for post-mortem diagnosis of MI depends on the stage in which the autopsy occurs.…”
mentioning
confidence: 99%
“…The electrocardiogram 2 and the echocardiogram [3][4][5][6][7][8][9][10][11][12][13][14][15] are noninvasive methods capable of identifying the area of necrosis or scarring. Although it identifies the presence of an MI-dependent electrically inactive area, the ECG is not a method that can quantify the infarction area 2 .…”
mentioning
confidence: 99%